Ответы и объяснения

  • Участник Знаний
2013-12-20T13:20:12+04:00
3X - 5Y = 8   ( * ( -2))
- 6X + 10Y = - 16
  6X + 3Y = 3
..............................
13Y = - 13
Y = - 1
3X + 5 = 8
3X = 3
X = 1
ОТВЕТ X = 1    Y = ( - 1 )

   
2013-12-20T13:21:59+04:00
3x-5y=8    все умножить на -2          
6x+3y=3


-6x+10y=-16                               6х-3=3
6x+3y=3                                     6х=3+3
________                                    6х=6
13у=-13                                       х=1
у=-1

Ответ (1;-1)
Если 3 * ( -1) будет ( -3), а не 39
ой блин я умножил на(-13) )))
хD
спасибо вам обоим
нез